One-layer pancreaticojejunostomy using reinforcing sutures in pancreaticoduodenectomy: A single surgeon’s experience with 122 cases - Yun Kyung Jung; Dongho Choi; Kyeong Geun Lee (Asian Journal of Surgery, 2021)
Background: Discussions about pancreaticojejunostomy (PJ), which can reduce the incidence of postoperative pancreatic fistula (POPF) in pancreaticoduodenectomy (PD), are ongoing. Here we introduce the surgical technique of PJ performed at our hospital and analyze its safety and advantages. Methods: We retrospectively analyzed 122 patients who underwent one-layer PJ using reinforcing sutures in PD. PJ was performed with reinforcing sutures on the pancreatic stump, including the insertion of a soft silastic catheter for internal drainage followed by suturing of the pancreas and jejunum with one layer. Results: Of the 122 patients who underwent PJ with this technique, 62 (50.8%) developed POPF. However, 37 (30.3%) had grade A that did not affect the hospital course. Critical POPF occurred in 25 patients: grade B in 20 (16.4%) and grade C in 5 (4.1%). There was no significant difference in the critical POPF patient group according to the pancreas related disease related to pancreatic texture. Conclusion: Although this technique cannot prevent POPF, we noted no significant difference in POPF versus other surgical techniques. In addition, this technique, which was designed to increase pancreatic texture, is practical and simple for PJ. Therefore, the inexperienced hepatobiliary and pancreatic surgeon can perform it without major complications.